2024
DOI: 10.1038/s12276-023-01151-5
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the molecular mechanisms of stem cell dynamics in hair follicle regeneration

Jung Hyun Lee,
Sekyu Choi

Abstract: Hair follicles, which are connected to sebaceous glands in the skin, undergo cyclic periods of regeneration, degeneration, and rest throughout adult life in mammals. The crucial function of hair follicle stem cells is to maintain these hair growth cycles. Another vital aspect is the activity of melanocyte stem cells, which differentiate into melanin-producing melanocytes, contributing to skin and hair pigmentation. Sebaceous gland stem cells also have a pivotal role in maintaining the skin barrier by regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 138 publications
0
5
0
Order By: Relevance
“…Another important feature of the hair follicle is immune privilege ( Paus et al, 2003 ; Bertolini et al, 2020 ; Lee and Choi, 2024 ). The immune privilege is a set of mechanisms that prevent or suppress active cytotoxic attacks from immune cells to prevent potential damage of organs by inflammatory processes.…”
Section: Regulation Of the Immune Privilege Of Hair Folliclesmentioning
confidence: 99%
“…Another important feature of the hair follicle is immune privilege ( Paus et al, 2003 ; Bertolini et al, 2020 ; Lee and Choi, 2024 ). The immune privilege is a set of mechanisms that prevent or suppress active cytotoxic attacks from immune cells to prevent potential damage of organs by inflammatory processes.…”
Section: Regulation Of the Immune Privilege Of Hair Folliclesmentioning
confidence: 99%
“…Recently, a study showed that when a superficial wound was created in mice, the HF cells in the newly formed epidermis were gradually replaced by keratinocytes derived from the epidermis ( Ji et al, 2021 ). It is indicated that HFSCs in the bulge region predominantly react to epidermal wounds by generating short-lived “transient amplifying” cells, which play a part in the recovery of acute wounds ( Lee and Choi, 2024 ). Langton et al reported that when a wound was created in the tail of mutant mice lacking all HF development, the cutaneous wounds healed with a delay re-epithelialization ( Langton et al, 2008 ).…”
Section: Hfscs In Epidermal Regenerationmentioning
confidence: 99%
“…Hence, the importance of epidermal stem cells lies in their ability to repair skin defects, restore skin integrity, enhance tensile strength, and improve barrier function ( Singer et al, 1999 ). During wound healing and skin regeneration, epidermal stem cells acquire the ability to repair adjacent compartments, and these compartments can be refilled with each other ( Sada et al, 2016 ; Hirsch et al, 2017 ; Lee and Choi, 2024 ). Observed that mechanical stretching and epidermal stem cells are closely correlated and regulated by EZH2 ( Wang et al, 2021 ; Wang et al, 2021 ).…”
Section: Hfscs In Epidermal Regenerationmentioning
confidence: 99%
“…The mesenchymal components of the HF, i.e., the dermal sheath, also contain SCs called dermal sheath mesenchymal stem cells or HF dermal stem cells that are capable of self-renewal and regeneration of the dermal sheath compartment after catagen [116]. The HF-associated sebaceous glands also contain Lrig1+ SCs and SCD1+ proliferative progenitor cells that differentiate into sebocytes [117]. The markers of different SCs within the HF components include CD200 (human), CD34, K19, Sox9, Lgr5, Hopx, Nfatc, Tcf, Lhx2 and Gli1 for the bulge SCs; Lgr6, Lrig1 and MTS24 for the isthmus SCs; Blimp1 for the sebaceous gland and Sca1 for the infundibulum [118].…”
Section: Hair Folliclesmentioning
confidence: 99%